Salicylic acid induces acclimation to water deficit in Phaseolus lunatus genotypes - Jakeline M. da Silva; José L. de Araújo; Henarmmany C. A. de Oliveira; Larisse B. S. Pereira; Marcus V. L. Sperandio; Natália M. Corte-Real; Cláudia Ulisses (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT In Brazil, the lima bean is the second most economically significant legume within the genus Phaseolus. Climate change, particularly water scarcity, threatens the production of this species. The application of salicylic acid has mitigated the adverse effects of stress. This study aimed to assess the impact of salicylic acid on acclimatisation to water restriction in three genotypes of Phaseolus lunatus (‘Cara Larga’, ‘Cearense’, and ‘Orelha de Vó’). A completely randomised design with a triple factorial included three broad bean genotypes, two pre-conditionings with 1.0 mM salicylic acid and without this elicitor (0.0 mM), and three levels of water availability (75, 50, and 25%), totalling 18 treatments with eight replicates. Physiological and biochemical responses were evaluated after 60 days of treatment. The responses varied among the genotypes. ‘Cara Larga’ stood out regarding osmoregulatory and antioxidant parameters compared to the other genotypes. In contrast, ‘Cearense’ showed an increase only in carbohydrates and carotenoids concentrations, while ‘Orelha de Vó’ exhibited more efficient water use and higher levels of proline under greater water restriction, concurrently with a decline in other parameters. Overall, the ‘Cara Larga’ genotype appears to be the most responsive to the modulating effects induced by acid application, especially under a water restriction of 25%. Applying, applying salicylic acid under conditions of low water availability may be a strategy for modulating the synthesis of osmoregulatory and antioxidant responses in P. lunatus.